Securities lending and information acquisition - Stefan Greppmair; Stephan Jank; Pedro A. C. Saffi; Jason Sturgess (Deutsche Bundesbank, 2024)
Using microdata on stock-level lending positions from German mutual funds, we show that active funds use the equity lending market to obtain information about short sale demand. Funds reduce long positions in response to these demand signals, which allows fund managers to front-run public disclosure of big short positions and avoid future losses. Fund managers exploit this information advantage across funds they manage, but do not share it within their fund family, consistent with short demand signals providing an information advantage. Our results suggest a new motive for securities lending and an information aggregation role for the equity lending market.
Keywords: G10; G12; G14; G18; 330; Equity lending markets; mutual funds; short sales; short interest; price revelation; public disclosure